implementation of Project-Based Learning (PBL) in Learning Evaluation Courses Reviewed from Learning Activities in History Education Students Program at Universitas PGRI Argopuro Jembe: Implementasi Project Based Learning (PBL) Mata Kuliah Evaluasi Pembelajaran Di Tinjau Dari Aktivitas Belajar Pada Mahasiswa Program Studi Pendidikan Sejarah Universitas PGRI Argopuro Jember - M. Iqbal Ibrahim H; Rina Rohmawati; Ahmad Zaki Emyus (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to analyze the implementation of project based learning in the learning evaluation course for students of the History Education Study Program at Universitas PGRI Argopuro Jember. Focus of his research is on the form of implementation of project based learning in learning evaluation courses, the results of implementing project based learning and student learning activities, as well as student responses regarding project based learning. The approach used is qualitative with descriptive method and determining informants with purposive sampling technique. That is, the data obtained in this study is presented in the form of written words from the observed object and has been determined. Data collection techniques are in the form of observation sheets and interviews. the results of the research are as follows: a) the form of implementing project based learning for students in the form of observation, interview and documentation assignments in 12 school locations in Jember Regency; b) implementation results show data on 12 schools from various levels of education along with their curricula. Student learning activities have increased with the acquisition of new skills and experiences after the activity; c) Students learning activities also showed positive changes, with various new experiences and skills gained during the activity. This is reflected in the table of student learning activity evaluation results, with an average score of 29.3 per group and a percentage of 91.61%. the implementation of project based learning received a good response from students to be reapplied to other courses